Metal–organic framework-derived carbon decorated Ni–Sn nanostructures for ultrastable metal-ion batteries. (June 2021) - Shang, Huan; Jin, Danqing; Ke, Longwei; Hu, Kang; Wang, Xueyou; Ding, Ying; Lin, Huijuan; Rui, Kun; Zhu, Jixin; Huang, Wei
Abstract: Sn-based anode materials have been considered with great potential for advanced metal-ion batteries contributed to their fascinating cost efficiency and relatively high theoretical capacity. Nevertheless, their severe volume expansion hinders the commercial applications. Herein, a facile strategy has been proposed to design carbon nanotube-decorated Ni–Sn nanostructures (Ni–Sn@CNT) via catalytic conversion from the Ni-MOF@SnO2 precursor. In such unique architecture, the metallic Ni acts as a buffer matrix (electrochemically inactive phase) to effectively suppress the unfavorable volume variation of Sn during the long-term battery operation and the conductive CNT network offers sufficient electron and ion transport pathway. Benefitting from these features, the as-prepared Ni–Sn@CNT nanostructures harvest a decent capacity of 408.7 mAh g −1 and 91 mAh g −1 for storing Li + and Na + after 500 cycles, respectively. Highlights: CNTs decorated Ni–Sn was synthesized via pyrolysis of metal organic frameworks. Highly conductive CNT networks facilitate electron transportation. Electrochemical inactive Ni buffers the volume change of Sn during cycling. The as-designed electrode delivers satisfactory electrochemical performance.